Systems research experiences in Africa - Kategile, J.A.; Smith, O. (Alberta University, 1993)
The Animal Production Systems Research (APSR) was introduced to sub-Saharan African National Agricultural Research Systems (NARs) in mid-1980's by the International Agricultural Research Centres (IARCs) and donors. APRS was accepted by NARs after realizing that the traditional on-station research had failed to make any impact in the rural community. IARC's and donor support is still needed in 1990's. The adoption of APSR approach has been slow primarly because of weaknesses in NARS due to lack of a critical mass of scientists in the majority of the NARs and inadequate funding. However, some NARS have adopted APSR in different ways, inorder to fit the weak socio economic component in APSR teams. Diagnostic surveys were carried out with some difficulties and data arising from them took a long time to analyse, some have not been fully analyzed. Some APSR teams skipped the diagnostic phase. The weakness is also reflected in the scarcity of economic analysis in the majority of the APSR programmes. For the futur, African countries should aim at developing small research teams of the right compliment for effective APSR. Foreign expatriates are placed where they fill gaps on a temporary basis. On long term basis, training will only be effective if retention of staff is improved. The adoption of introduced technologies by farmers have been very good in cases where farmers have obtained obvious benefits of more income, milk supplies and increased crop production (through manure). Alternative technologies bringing minor benefits to the farmers. Research - extension linkages developed when extension services were strong and failed to emerge in the converse situations. On the extreme some APSR teams assumed the roles of extension and encouraged the formation of grass root farmer organizations. This Development needs close scrutiny. APSR teams should always link with develop institutions (extension, NGOs, and farmers organizations) to ensure sustainability. It is deduced that APSR approach has a potential to bring about an impact in sub-Saharan Africa. In spite of the obvious weakness of NARs and inability to utilise the traditional APSR research methodologies. APSR has been effective and should be encouraged and supported. For the future, APSR teams have to cope with arising issues of integration with crops and trees, conservaiton, environment and gender.